Bioactive Compounds of Marine Algae and Their Potential Health and Nutraceutical Applications: A Review - Emin Cadar; Antoanela Popescu; Ana-Maria-Laura Dragan; Ana-Maria Pesterau; Carolina Pascale; Valentina Anuta; Irina Prasacu; Bruno Stefan Velescu; Cezar Laurentiu Tomescu; Claudia Florina Bogdan-Andreescu; Rodica Sirbu; Ana-Maria Ionescu (Marine Drugs)
Currently, marine algae are still an under-exploited natural bioresource of bioactive compounds. Seaweeds represent a sustainable source for obtaining bioactive compounds that can be useful for the fabrication of new active products with biomedical benefits and applications as biomedicinals and nutraceuticals. The objective of this review is to highlight scientific papers that identify biocompounds from marine macroalgae and emphasize their benefits. The method used was data analysis to systematize information to identify biocompounds and their various benefits in pharmaceuticals, cosmetics, and nutraceuticals. The research results demonstrate the multiple uses of seaweeds. As pharmaceuticals, seaweeds are rich sources of bioactive compounds like polysaccharides, protein compounds, pigments, and polyphenols, which have demonstrated various pharmacological activities such as antioxidant, antibacterial, anti-inflammatory, antiviral, anticoagulant, and potentially anticarcinogenic effects. Seaweed has gained recognition as a functional food and offers a unique set of compounds that promote body health, including vitamins, minerals, and antioxidants. In conclusion, the importance of this review is to expand the possibilities for utilizing natural resources by broadening the areas of research for human health and marine nutraceuticals.